2009
DOI: 10.1097/wnr.0b013e328323ab07
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of multisensory integration by modality-specific attention in aging

Abstract: Previous research demonstrates that modality-specific selective attention attenuates multisensory integration in healthy young adults. Additionally, older adults evidence enhanced multisensory integration compared to younger adults. We hypothesized that these increases were due to changes in top-down suppression, and therefore older adults would demonstrate multisensory integration while selectively attending. Performance of older and younger adults was compared on a cued discrimination task. Older adults had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
91
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(103 citation statements)
references
References 20 publications
9
91
2
Order By: Relevance
“…An audiovisual WM task version with irrelevant stimuli from the auditory modality interleaved between relevant visual stimuli or vice versa also did not reveal an age-related cross-modal suppression deficit (Guerreiro et al, submitted for publication). In general, evidence from these studies agrees with prior cross-modal research in aging, which consistently demonstrates preserved multisensory performance in aging in the face of unisensory cognitive decline, notably in the visual domain (Hugenschmidt et al, 2009a, 2009b; Laurienti et al, 2006). This body of work suggests that older adults may benefit most when functioning within multisensory than unisensory environments.…”
Section: External Interference Resolution Across the Lifespansupporting
confidence: 88%
“…An audiovisual WM task version with irrelevant stimuli from the auditory modality interleaved between relevant visual stimuli or vice versa also did not reveal an age-related cross-modal suppression deficit (Guerreiro et al, submitted for publication). In general, evidence from these studies agrees with prior cross-modal research in aging, which consistently demonstrates preserved multisensory performance in aging in the face of unisensory cognitive decline, notably in the visual domain (Hugenschmidt et al, 2009a, 2009b; Laurienti et al, 2006). This body of work suggests that older adults may benefit most when functioning within multisensory than unisensory environments.…”
Section: External Interference Resolution Across the Lifespansupporting
confidence: 88%
“…As a result of selective attention to the visual modality, visual stimulus processing may have been enhanced relative to auditory stimulus processing (e.g., McDonald et al, 2005;Spence & Parise, 2010). It has been shown that selectively attending to only one sense also modulates multisensory integration of sensory information of that and another sensory modality (e.g., Hugenschmidt, Mozolic, & Laurienti, 2009;Mozolic, Hugenschmidt, Peiffer, & Laurienti, 2008;Talsma, Doty, & Woldorff, 2007). In some cases, modality-specific attention even reduced multisensory response enhancement to statistical facilitation (see Mozolic et al, 2008, Fig.…”
Section: Discussionmentioning
confidence: 96%
“…For instance, older adults exhibit baseline increases in multisensory integration during modality-specific attention (Hugenschmidt et al, 2009), and, increased distraction from ambient sensory information within the experimental environment (Stevens et al, 2008). During passive viewing of repeating objects superimposed over novel scenic images, Chee et al (2006) found that visual cortical adaptation to objects was preserved in young adults but impaired in older adults.…”
Section: Discussionmentioning
confidence: 99%